Energy and life cycle impact assessment for xylitol production from corncob - Dasgupta, Diptarka; Sidana, Arushdeep; Ghosh, Prasenjit; Sharma, Tripti; Singh, Jasvinder; Prabhune, Asmita; More, Snehal; Bhaskar, Thallada; Ghosh, Debashish (Journal of Cleaner Production, 2021)
The conversion of biobased feedstocks into energy and value-added chemicals is one main approach to address the current global challenge for waste mitigation through the biorefinery mode. Corncob biomass which is one of the most abundant agricultural residue in India with a high hemicellulose content, can serve as a potential low-cost raw material for food-grade xylitol production. The present study demonstrates a process for xylitol production from corncob biomass with detailed energy and life cycle analysis for viability assessment. The major highlight of the process is the use of microbial fermentation, where biomass-derived D-xylose is converted to xylitol with high selectivity. Overall, 0.502 kg of xylitol crystals could be produced from 3.5 kg of corncob biomass. Simulation analysis revealed that the evaporators are the primary consumers of energy, and the process of heat integration can significantly reduce the energy requirements of the overall process. Environmental impacts of the system evaluated showed emission results of 8.68 kg CO2 equivalent and revealed that marine aquatic and freshwater eco-toxicity are the only possible contributors to the environment. The results suggest that the process would have favourable energy balances, which can be used in pilot plant and heat exchanger network design and operation for xylitol production scale up to 500 L. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: biomass valorization; Life cycle impact assessment; simulation; xylitol

Enzymatic biodegradation of used engine oil using a novel lipase derived from renewable feedstocks - Tracy, Preetanshika; Dasgupta, Diptarka; Ashok, Patel Pratima; More, Snehal; Sarkar, Bipul; Porwal, Jyoti; Tripathi, Deependra (World Journal of Microbiology & Biotechnology, 2025)
This study introduces an eco-friendly enzymatic approach for biodegrading used engine oil, utilizing a novel lipase from the mesophilic yeast strain Pichia Caribbica. The yeast was cultured in detoxified corncob hydrolysate with used cooking oil as an inducer. OVAT study confirmed that the optimal pH and temperature for lipase production by the strain was 7.0 and 25 degrees Celsius, respectively, with lipase activity of 70 IU/mL. The enzyme effectively degraded similar to 46% of used engine oil over a period of 15 days. Gas Chromatography-Mass Spectrometry (GC-MS) and FT-IR analysis confirmed a significant reduction in hydrocarbon concentrations and the emergence of new functional groups, confirming the enzyme's ability to degrade complex hydrocarbons into less toxic derivatives. These findings highlight the lipase's potential as an effective biocatalyst for eco-friendly bioremediation of oil-contaminated environments, such as soils and aquatic systems, while also emphasizing its role in environmental management through the reuse of waste by-products in enzyme production, thus reducing the environmental impact of improper waste disposal.
Keywords: Biodegradation; Lipase; PC5703; Used cooking oil; Used engine oil